Five ways to get a grip on patient safety in UGME curriculum: Exploring the current landscape and future positioning - Khemani, Ekta; Hunjan, Sanjum (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Efforts to increase patient safety have increased over the past 20 years. Education in patient safety has historically targeted residents, senior physicians, and healthcare professionals. Recently, patient safety has been identified as a top priority that should be instilled in the earliest stages of medical education, targeted at medical students. This Black Ice paper is intended to help readers to get a grip on how to manage barriers associated with reporting of medical errors, analysis of patient safety incidents, and integration of patient safety education curricula into existing courses and rotations.